Dynamic changes in mitochondrial DNA, morphology, and fission during oogenesis of a seasonal-breeding teleost, Pampus argenteus. (October 2021) - Yang, Yang; Ning, Chao; Li, Yaya; Wang, Yajun; Hu, Jiabao; Liu, Yifan; Zhang, Man; Sun, Yibo; Gu, Weiwei; Zhang, Youyi; Sun, Jiachu; Xu, Shanliang
Highlights: Mitochondrial morphology and distribution are stage-specific during oogenesis. Mitochondria might participate in the vitellogenesis of oocyte mff -mediated mitochondrial fission may play a crucial role in oocyte development Abstract: Mitochondria play crucial roles during oocyte development. In this study, we have investigated mitochondrial morphology, mtDNA, Ca 2+ -ATP enzyme activity, and mitochondrial fission factor ( mff ) expression levels during oogenesis of the silver pomfret Pampus argenteus . The mtDNA increased with oocyte development, and mitochondrial morphology and distribution were stage-specific. In the perinucleolar oocytes, oval mitochondria were dispersed in the cytoplasm. In previtellogenic oocytes, mitochondria massively increased and aggregated, forming mitochondrial clouds. At the same time, two morphologically different types of mitochondria had been distinguished, one of which was elongated with well-developed cristae, and the other was round with distorted and fused cristae. During vitellogenesis, the increases in mitochondria with well-developed cristae and in Ca 2+ -ATPase enzymatic activity were accompanied by an accumulation of yolk substance, suggesting the possible participation of mitochondria in the formation of vitellogenesis. Furthermore, we examined the cDNA of mff its transcript levels in relation to oocyte development. The transcript levels of mff were high in the perinucleolar stage, increasing to the highest level at the previtellogenic stage. Immunocytochemistry showed that MFF was detected in the cytoplasm of previtellogenic and midvitellogenic oocytes. We speculated that the mff -mediated mitochondrial fission may play a crucial role in oocyte development, especially in vitellogenesis.